PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PEMANFAATAN JASA PARIWISATA SWING DI KECAMATAN TEGALLALANG, KABUPATEN GIANYAR - I Made Yogi Darmawan; Si Ngurah Ardhya; Komang Febrinayanti Dantes (Universitas Pendidikan Ganesha, 2023)
The purpose of this study is to determine (1) the factors causing accidents from the legal perspective in the utilization of swing tourism services in Tegallalang District, Gianyar Regency, and (2) to find out how the implementation of provisions concerning the safety and security of tourists related to the use of swing tourism services in Tegallalang District, Gianyar Regency. The type of research used is empirical legal research with a descriptive research nature. The location of this research was conducted in Tegallalang District, Gianyar Regency. The data collection techniques used are by means of document studies, observations, and interviews. The sample determination technique used is the Non-Probability Sampling technique and the determination of the subject using Proposive Sampling. The technique of processing and analyzing data qualitatively. The results of the study show that (1) the factors causing accidents from the legal perspective in the utilization of swing tourism services in Tegallalang District, Gianyar Regency stem from the indifferent attitude of business actors and consumers in applying the applicable rules, but on the other hand, the lack of rules governing the SOP of the swing also increases the accident factor from using the service. Then (2) the implementation of provisions concerning the safety and security of tourists related to the use of swing tourism services in Tegallalang District, Gianyar Regency has not been fully implemented properly. Starting from the lack of legal substance, the structure that does not carry out tasks well to the legal culture of the community that is lacking in the ongoing swing tourism activities.